2005
DOI: 10.1007/s00595-004-2962-7
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Gene Expression Analysis by cDNA Microarray During Liver Regeneration After Partial Hepatectomy in Rats

Abstract: The quantitative gene expression profiles have important implications, warranting further investigation of the genetic mechanisms involved in the process of liver regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 26 publications
0
8
1
Order By: Relevance
“…In the rat, hepatocytes start entering S phase after 12 h and peak DNA synthesis occurs by 24 h after PHx, followed ϳ24 h later by proliferation of nonparenchymal cells (38). During the initial 24 h following PHx an extensive program of gene expression changes is activated, as previously demonstrated by our group and others (9,19,23) (R. Vadigepalli, unpublished data).…”
mentioning
confidence: 52%
“…In the rat, hepatocytes start entering S phase after 12 h and peak DNA synthesis occurs by 24 h after PHx, followed ϳ24 h later by proliferation of nonparenchymal cells (38). During the initial 24 h following PHx an extensive program of gene expression changes is activated, as previously demonstrated by our group and others (9,19,23) (R. Vadigepalli, unpublished data).…”
mentioning
confidence: 52%
“…4 In our previous study of liver regeneration after PH, we showed that the variations in gene expression could be classified into 72 different patterns via a mass survey of gene expression by cDNA microarray. 5 We also discovered that the isolated hepatocytes have a stem cell-like strong proliferation ability and can repopulate extensively in the host liver after suitable preconditioning treatment of recipients in liver transplantation. 6 Liver regeneration constitutes a conditional cell renewal system that may proceed under well-defined conditions such as PH.…”
Section: Introductionmentioning
confidence: 98%
“…In rats and mice, partial hepatectomy triggers a sequence of regeneration events from the first 30 minutes to 7 days after the procedure. A large number of genes with either new or increased expression in the regenerating liver have been identified and categorized into several phases of activity, including immediate-early, delayed, cell cycle, and DNA replication and mitosis genes [3], [4].…”
Section: Introductionmentioning
confidence: 99%